Tat Twam Asi and Derrida’s Differance for a Greener Accounting - Putu Yudha Asteria Putri (International Journal of Religious and Cultural Studies, 2021)
This article aims to present a cultural accounting research methodology that is local as well as religious to construct a greener accounting. Construction methodology employed was substantive interrelationships between Jacques Derrida's thought of “differance” and an alternative path called Tat Twam Asi as the teachings of chastity without limits. The meaning contained in the teachings of Tat Twam Asi is "he is you, I am you, and all beings are the same". The result proves thatpresently accounting has been formed from the social, cultural, political, economic, ideological dimensions, and there is no room for God. Green accounting serves only as an economic reality. Through this extended methodology of Derrida and Tat Twam Asi, a greener accounting can be reconstructed.